Proszępomóżcie
Wykonaj redukcję wyrazów podobnych
12ab – a - b + 3ab =
10ab - 3a2b + 7ab - 7a2b=
2xy - 3x2y + 4xy2 - 5xy =
7x – 8x2 – 3x – 9x2 -1=
9y - 10x -5y +15x +7=
12 x2y – 13xy - 10 x2y +13xy =


Odpowiedź :

Cześć!

Szczegółowe wyjaśnienie:

a)

[tex]12ab - a - b + 3ab = 15ab - a - b[/tex]

b)

[tex]10ab - 3a {}^{2} b + 7ab - 7a {}^{2} b \\ 17ab - 10a {}^{2} b \\ ab(17 - 10a)[/tex]

c)

[tex]2xy - 3x {}^{2} y + 4xy {}^{2} { - 5xy } \\ - 3xy - 3x {}^{2} y + 4xy {}^{2} \\ - xy(3 + 3x - 4y)[/tex]

d)

[tex]9y - 10x - 5y + 15x + 7 = \\ 4y + 5x + 7[/tex]

e)

[tex]12x {}^{2} y - 13xy - 10x {}^{2} y + 13xy = \\ 2x {}^{2} y[/tex]

Pozdrawiam,

MrBarte!